Systematic review assessing the measurement properties of patient-reported outcomes for venous leg ulcers. Issue 5 (13th November 2017) - Poku, E; Aber, A; Phillips, P; Essat, M; Buckley Woods, H; Palfreyman, S; Kaltenthaler, E; Jones, G; Michaels, J
Abstract: Background: A variety of instruments have been used to assess outcomes for patients with venous leg ulcers. This study sought to identify, evaluate and recommend the most appropriate patient-reported outcome measures (PROMs) for English-speaking patients with venous leg ulcers. Methods: This systematic review used a two-stage search approach. Electronic searches of major databases including MEDLINE were completed in October 2015, and then updated in July 2016. Additional studies were identified from citation checking. Study selection, data extraction and quality assessment were undertaken independently by at least two reviewers. Evaluation and summary of measurement properties of identified PROMs were done using standard and adapted study-relevant criteria. Results: Ten studies with data for four generic PROMS and six condition-specific measures were identified. No generic PROM showed adequate content and criterion validity; however, the EuroQoL Five Dimensions (EQ-5D™), Nottingham Health Profile (NHP) and 12-item Short-Form Health Survey (SF-12 ® ) had good acceptability. In general, the EQ-5D™ showed poor responsiveness in patients with venous leg ulcers. Most condition-specific PROMs demonstrated poor criterion and construct validity. Overall, there was some evidence of internal consistency for the Venous Leg Ulcer Quality of Life (VLU-QoL) and the Sheffield Preference-based Venous Ulcer questionnaire (SPVU-5D). Test–retest reliability was satisfactory for the Venous Leg Ulcer Self-Efficacy Tool (VeLUSET). Conclusion: The NHP and VLU-QoL questionnaire seemed the most suitable PROMs for use by clinicians. However, a valid condition-specific PROM is still required. Graphical Abstract: The aim of the current review was to identify, evaluate and recommend the most appropriate patient-reported outcome measures (PROMs) for English-speaking patients with venous leg ulcers (VLUs) in clinical practice. The Nottingham Health Profile (NHP) and Venous Leg Ulcer Quality of Life (VLU-QOL) are considered to be the most suitable PROMs for use. Valid disease-specific PROM required